Efflux Pump-Binding 4(3-Aminocyclobutyl)Pyrimidin-2-Amines Are Colloidal Aggregators - Tania Szal; Shweta Singh Chauhan; Philipp Lewe; Fatima-Zahra Rachad; Marina Madre; Laura Paunina; Susanne Witt; Ramakrishnan Parthasarathi; Björn Windshügel (Biomolecules, 2023)
Efflux pumps are a relevant factor in antimicrobial resistance. In E. coli, the tripartite efflux pump AcrAB-TolC removes a chemically diverse set of antibiotics from the bacterium. Therefore, small molecules interfering with efflux pump function are considered adjuvants for improving antimicrobial therapies. Several compounds targeting the periplasmic adapter protein AcrA and the efflux pump AcrB have been identified to act synergistically with different antibiotics. Among those, several 4(3-aminocyclobutyl)pyrimidin-2-amines have been shown to bind to both proteins. In this study, we intended to identify analogs of these substances with improved binding affinity to AcrA using virtual screening followed by experimental validation. While we succeeded in identifying several compounds showing a synergistic effect with erythromycin on E. coli, biophysical studies suggested that 4(3-aminocyclobutyl)pyrimidin-2-amines form colloidal aggregates that do not bind specifically to AcrA. Therefore, these substances are not suited for further development. Our study emphasizes the importance of implementing additional control experiments to identify aggregators among bioactive compounds.